Investigating the Effects of Different Model Based Inquiries on Students' Science Achievement, Scientific Process Skills and Motivation - Gecgil, Tugba; Akcay, Hakan (NECMETTIN ERBAKAN UNIV, 2024)
In this research, the effects of using Model -Based and Argumentation -Supported Model -Based Inquiry methods on 6th - grade middle school students' knowledge, scientific process skills, and motivation regarding the subject of sound and its properties were examined according to the current curriculum. A total of 77 students attending a state school participated in the study that employed a mixed research design. In the semi -experimental study, two experimental groups and one control group were used. Lessons were taught according to the model -based inquiry method supported by argumentation in the first experimental group, according to the model -based inquiry method in the second experimental group, and according to the current curriculum in the control group. In the research, achievement tests, scientific process skills tests, and motivation scales were administered as pre-tests and post-tests for data collection. The obtained data were analyzed using One -Way Analysis of Covariance (ANCOVA). According to the obtained results, it has been determined that the Model -Based and ArgumentationSupported Model -Based Inquiry methods significantly differ from the current curriculum in terms of student achievement and motivation. Furthermore, it has been observed that the Argumentation -Supported Model -Based Inquiry method is more effective than the Model -Based Inquiry method in enhancing students' development of scientific process skills.
Keywords: Model based inquiry; Argumentation; Science education; Education & Educational Research